The effect of Meta Cognitive Therapy (MCT) on couple communication patterns in patients with coronary heart diseases (CHD) - Sara Hashemi; Akbar Nikpajooh (مجله علوم روانشناختی, 2018)
Research shows that coronary heart disease is one of the main couses of death and disability in the world which reduces the useful efficacy of people. According to the background mental factors can affect on many aspects of life. Therefore if applying psychological interventions to adjust and improve the restrictions imposed into the lives of patients is essential? This study evaluates the efficacy of meta cognitive therapy on patients with coronary heart disease (CHD) in a semi- experimental design with control and experimental group and consists of pre and post testing. 30 members of Rajayi hospital were selected through convenience sampling and were divided into control and experimental groups by accident. After responding to couple communication patterns questionnaire, experimental group received intervention for 8 sessions about 2 hours every week. Control group did not receive any psychological therapy. The results show that this intervention has improved couple communication patterns significantly (0.001) among CHD patients. This means that training meta cognitive approach led to improvement of couple communication patterns in experimental group.